A Highly Efficient and Linear Class AB Power Amplifier for RFID Application - Sepideh Fazel; Javad Javidan (Bulletin of Electrical Engineering and Informatics, 2015)
Power amplifiers (PAs) are usually the largest consumer of power in the transmitter. Therefore, designing a high efficiency RF power amplifier might be the best solution to cope with the problem of battery lifetime limitations in portable RFID code reader. In this paper, the designed circuit in Agilent ADS software is implemented using 0.18 μm RFCMOS technology at 3.3 v supply voltage. The measured results indicate that power added efficiency,out put power and power gain of the proposed class AB power amplifier at frequency of 2.4GHz are 35% , 30dBm and 28dBm.